ROS-scavenging and immunomodulatory MXene-MnO₂ hydrogel nerve conduit for peripheral nerve regeneration - Tiankun Hui; Yajing Yang; Fei Diao; Haihan Fan; Jie Chen; Yan Li; Yingjie Song; Chenchen Fu; Meijie Jia; Wenwei Han; Tengbo Yu; Jianye Fu (Chemical Engineering Journal, 2026)

Characterization of a novel Era-homolog (AtERG1) in Arabidopsis that is essential for chloroplast development - Yi Lin; Shuangyuan Jia; Chenchen Zhang; Shanshan Chen; Han Xiang; Jiaqi Chen; Ying Yang; Jiawei Chen; Ming Li; Jinwen Liu (Journal of Plant Biochemistry and Biotechnology, 2026)

Particle Type- and Morphology-Associated Neurotoxicity of Microplastics and Nanoplastics via Divergent PPARγ Modulation in Zebrafish - Chenchen Han; Lixia Peng; Xinlei Guo; Yaqi Yu; Mingming Niu; Willie J.G.M. Peijnenburg; Zhiqiang Li; Xilin She; Chuanhong Wu; Lianzhen Li (Journal of Hazardous Materials, 2026)

In-situ heterojunction on high-aspect-ratio cellulose nanocrystals for long-range charge transport in e-skin - Chenchen Shen; Weiwei Chen; Lin Guo; Yanrui Zou; Shuan Han; Ning Yu; Lin Gan; Jin Huang (Carbohydrate Polymers, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

Sustainable alternative to biochar: Effects of oxychar on soil carbon sequestration pathway and microbial communities - Cheng Ji; Chenchen Zhao; Shutao Wang; Qinggang Meng; Huiwei Zhao; Yifan Li; Duo Li; Mingzhen Xing; Shiming Su; Bing Han; Wei Liu (Journal of Environmental Sciences, 2026)

Engineering a dynamic defect-mediated heterojunction anode for high-performance secondary batteries with liquid and solid-state electrolytes - Xiaofei Huang; Tianli Han; Ting Zhou; Yajun Zhu; Keke Wang; Fan Bu; Chenchen Zhang; Xuehui Wang; Jinyun Liu (Chemical Engineering Journal, 2026)

Cleavage of Beclin 1 by metacaspase 1 activates antiviral autophagy in plants - Rujian Hu; Qinglin Pi; Meng Yang; Wen Song; Zhihao Jiang; Chenchen Zhong; Huanxi Han; Cheng-Gui Han; Yongliang Zhang; Dawei Li (Molecular Plant, 2026)

pH/glutathione dual-responsive magnetic carboxymethyl chitosan nanoparticles for the controlled release of astaxanthin - Chenchen Li; Xintong Zhang; Weiye Xiu; Mingfu Yuan; Jingyang Wang; Diaomei Ma; Chunran Han (Innovative Food Science & Emerging Technologies, 2026)

Variation of surface chlorophyll-a concentration from 2003-2023 in the tropical western Pacific in response to the ENSO diversity - Gao Wei; Shi Xingyu; Cao Xiaowei; Han Yanyu; Zhang Sudong; Fan Haixia; Xu Chenchen; Ma Benjun (Journal of Marine Systems, 2025)

Mechanisms underlying tomato-mediated suppression of warmed-over flavor (WOF) and flavor enrichment in precooked stewed beef - Junmei Liu; Feng Huang; Dong Han; Chenchen Qi; Ping Yang; Chunhui Zhang; Christophe Blecker (Food Chemistry, 2025)

Synergistic effects of land use and sidewall cover on terrace sidewall stability in the tableland region of the Loess Plateau - Chenyun Bai; Changyan Yin; Ziyan Chen; Chenchen Ma; Sidra Sohail; Hanyang Tian; Jiangbo Qiao; Weixiang Cai; Xiaoyang Han; Yuanjun Zhu (CATENA, 2025)

Gas content and fracability in deep marine shales: Insights from laminar heterogeneity and reservoir characteristics - Xiao Xiao; Jizhen Zhang; Jianguo Wang; Wei Guo; Wei Lin; Denglin Han; Chenchen Wang (Journal of Environmental Chemical Engineering, 2025)

Highly flexible and large-scale hydrophilic nickel foam/MXene composite as a solar-driven interfacial evaporator for steam and electricity generation - ChenChen Kong; Ruiqi Xu; Na Wei; Xiaopeng Jiang; Zhijun Han; Panpan Cui; Hongzhi Cui (Chemical Engineering Journal, 2025)

A strategy for the development of receptor-containing antibodies targeting malaria variant surface antigens - Yizhuo Wang; Hengfang Tang; Jiarui Li; Wanxue Wang; Ming Li; Chenchen Zhu; Han Dai; Hongxin Zhao; Lubin Jiang; Bo Wu; Junfeng Wang (Science China Life Sciences, 2025)

High-cis astaxanthin nano lipid carrier: Preparation and bioavailability analysis - Chunran Han; Xintong Zhang; Chenchen Li; Jiaqi Sui; Xin Wang; Diaomei Ma; Jingyang Wang; Qi An (Food Bioscience, 2025)

Identification of the LBD Gene Family in Lettuce (Lactuca sativa) and Functional Analysis of LsLBD9 in Leaf Development - Chenchen Wang; Bin Zhang; Xue Liu; Xiangyang Han; Zhaoyang Xu; Kangting Dong; Jun Zhou; Dayong Li (Journal of Plant Growth Regulation, 2025)

Effect of Yeast Selenium on Growth Performance, Muscle Selenium Deposition, and Antioxidant Capacity of Juvenile Cherax quadricarinatus - Ying Han; Chenchen Wang; Jimin Deng; Lizhen Zhong; Xiao Huang; Yuandong Sun; Xiaojuan Cui (Fishes, 2025)
This study aimed to investigate the effects of organic selenium-enriched yeast on the growth performance, muscle selenium deposition, and antioxidant capacity of juvenile Cherax quadricarinatus. Five experimental diets supplemented with 0.00 (control), 1.00, 2.00, 3.00, and 4.00 mg/kg of selenium-enriched yeast were fed to crayfish with an average initial body weight of (6.35 ± 1.66) g for 56 days. On days 0, 14, 28, 42, and 56 of the trial, 10 crayfish from each group were randomly sampled for body weight measurement. On day 28, the body weight of the crayfish fed diets containing 1.00, 2.00, 3.00, and 4.00 mg/kg selenium-enriched yeast was significantly higher (p

N/O co-doped hollow sphere-like hard carbon with hierarchical pores for fast and high-capacity Na+/Li+ storage - Chenchen Bai; Bingjun Li; Chang Shu; Wenjie Chen; Yan Han; Dejun Li (Chemical Engineering Journal, 2025)

Performance of cut-off walls under long-term vacuum suction: A case study - Chenchen Xu; Yongtao Hu; Shijie Han; Geng Xueyu; Da Cheng; Ning He; Yongfeng Deng (Marine Georesources & Geotechnology, 2025)

Plasma Extracellular Matrix Protein 2 Level as a Predictive Biomarker for Rupture of Small Intracranial Aneurysms - Chenchen Wang; Yuwei Han; Da Huo; Xiaoming Li; Guobiao Liang (Journal of Molecular Neuroscience, 2025)

3D distribution of particulate organic carbon induced by the great whirl - Chenchen Zha; Sen Wang; Shiyao Ying; Hui Chen; Guoqing Han (Frontiers in Marine Science, 2025)
Mesoscale eddies can affect the distribution of matter in the ocean due to their inherent characteristics, thereby affecting local ecosystems. However, there are few previous studies on the influence of Great Whirl (GW) on the distribution of particulate organic carbon (POC). This study analyzes the influence of the GW on the three-dimensional distribution of marine POC concentration in the northwestern Indian Ocean, off the coast of Somalia. It is shown that there are significant differences in the spatial distribution modes of POC in the surface and subsurface ocean of GW. In the sea surface, the POC concentration at the edge of GW is higher than the eddy center resulting from the capturing and transporting effect of GW. The difference is about 20 mg·m −3 between the center and the edge. At the subsurface layer (approximately between 50 and 175 m), the concentration of POC in the eddy center is high, while that in the surrounding water is low. The maximum difference between the center and the edge can reach about 10 mg·m −3 . These phenomena show that GW will have an impact on the distribution of POC in the ocean, which in turn may affect the carbon cycle progress in the local ocean.

Pore-fracture fusion modeling method for ultra-deep clastic reservoirs - Hao Du; Binyu Ma; Chenchen Wang; Denglin Han; Rongrong Hu (Marine and Petroleum Geology, 2025)

Multi-level metabolic engineering of 6ʹ-sialyllactose in Escherichia coli - Chenchen Li; Mengli Li; Mo Han; Ming Miao; Tao Zhang (Food Bioscience, 2025)

Broad-spectrum anti-inflammatory and antioxidant therapy of inflammatory-storm actuated diseases via programmable self-derived cryo-dead neutrophils - Bin Li; Qiuxia Gao; Yunxia Wu; Hongyi Lei; Shengchao Ma; Wei Wang; Hang Sun; Weifeng Ma; Judun Zheng; Chenchen Yuan; Yunlong Zhang; Yue Jia; et al. (Chemical Engineering Journal, 2025)

Health impacts of PM2.5 emissions from brake pad wear: A comprehensive study on pulmonary, metabolic, and microbiota alterations - Li Zhou; Chenchen Song; Yuhan Lei; Lianlian Zhao; Yunlin Han; Yanfeng Xu; Baicun Li; Jianguo Guo (Toxicology, 2025)

STAT3 mediates ECM stiffness-dependent progression in ovarian cancer - Sun Chenchen; Qian Xueqian; Lu Yahui; Yuan Yi; Zhang Hui; Bai Lanning; Cheng Min; Han Yangyang (Molecular and Cellular Biochemistry, 2025)

Responses of various organic carbon pools to elevated temperatures in soils - Yafeng Han; Chenchen Qu; Xiping Hu; Pan Sun; Jie Kang; Peng Cai; Xingmin Rong; Wenli Chen; Qiaoyun Huang (Science of The Total Environment, 2024)

Unveiling energy transition strategy: A deep dive into China's ambitious renewable energy policy and its impact on carbon emission dynamics - Chenchen Song; Congyu Zhao; Zhengguang Liu; Xiaoyue Ma; Yongfa Yuan; Xiaojie Han (Journal of Cleaner Production, 2024)

Nonvisual system-mediated body color change in fish reveals nonvisual function of Opsin 3 in skin - Zihao Zhang; Chenchen Shi; Jian Han; Xiaoyu Ge; Na Li; Yang Liu; Jing Huang; Shixi Chen (Journal of Photochemistry and Photobiology B: Biology, 2024)

Anthraquinone centers modified covalent organic frameworks for boosted photocatalytic O2-to-H2O2 synthesis: Inhibiting the in-situ decomposition of H2O2 - Yu Luo; Chenchen Liu; Jiahui Liu; Xueming Liu; Yang Zhou; Xinwen Ou; Bo Weng; Jin Jiang; Bin Han (Chemical Engineering Journal, 2024)

Analysis of spatial and temporal characteristics of major natural disasters in China from 2008 to 2021 based on mining news database - Chenchen Yang; Han Zhang; Xunhua Li; Zongyi He; Junli Li (Natural Hazards, 2023)

Organic fertilization integrated with water management to remediate As and Cd contamination in a paddy soil - Pan Sun; Chenchen Qu; Zhenqian Xiong; Yafeng Han; Fuhai Ma; Peng Cai; Wenli Chen; Qiaoyun Huang (Science of The Total Environment, 2023)

Localized host-rock porosity near sealed fractures at 7 km depth: Geochemical evidence of deep-seated porosity controls - Denglin Han; Jizhen Zhang; Chenchen Wang; Wei Lin; Rui Yuan; Xin Nie; Juan Zhang (Journal of Structural Geology, 2023)

Construction of S-scheme Zn0.2Cd0.8S/biochar aerogel architectures for boosting photocatalytic hydrogen production under sunlight irradiation - Chonghai Deng; Lulu Peng; Xiaohui Ling; Tao Wang; Rui Xu; Yibin Zhu; Chenchen Wang; Xuehui Qian; Lili Wang; Yiping Wu; Hanmei Hu; Yongsheng Han (Journal of Cleaner Production, 2023)

The structure changes of microbial food web during the culture of grass carp larvae - Siqi Ma; Cui Feng; Mengqi Han; Chenchen Dong; Wenkai Chen; Jun Dou; Dapeng Li; Xiangjiang Liu (Aquaculture, 2023)

Balance dysfunction in large yellow croaker in response to ocean acidification - Xiaojie Wang; Yaoyi Feng; Zichao Zhang; Chenchen Li; Huan Han (Science of The Total Environment, 2023)

Effects of three processing technologies on the structure and immunoreactivity of α-tropomyosin from Haliotis discus hannai - Nairu Ji; Chenchen Yu; Xinyu Han; Xinrong He; Shuai Kang; Tianliang Bai; Hong Liu; Guixia Chen; Minjie Cao; Guangming Liu (Food Chemistry, 2023)

An antifouling gel-protected iridium needle sensor: Long-term, on-site monitoring of copper in seawater - Ying Li; Haitao Han; Chenchen Wang; Yan Liang; Dawei Pan; Haizeng Wang (Chemosphere, 2023)

ZnO quantum dots outperform nanoscale and bulk particles for enhancing tomato (Solanum lycopersicum) growth and nutritional values - Min Sun; Chenchen Zhao; Heping Shang; Yi Hao; Lanfang Han; Kun Qian; Jason C. White; Chuanxin Ma; Baoshan Xing (Science of The Total Environment, 2023)

Tip-porous microneedle: A highly stable sensing platform for direct determination of labile metals in natural seawater - Haitao Han; Jie Wang; Dawei Pan; Ying Li; Chenchen Wang (Environmental Pollution, 2023)

Concentration, Spatial-Temporal Distribution, and Bioavailability of Dissolved Reactive Iron in Northern Coastal China Seawater - Chenchen Wang; Yongsheng Luan; Dawei Pan; Yuxi Lu; Haitao Han; Shenghui Zhang (Journal of Marine Science and Engineering, 2022)
The concentrations of total dissolved iron (TdFe) and dissolved reactive iron (DrFe) in the Northern coastal China seawater (Yantai Sishili Bay) in 2018 were determined using cathodic stripping voltammetry (CSV). It was found that while the concentrations of TdFe ranged from 27.8 to 82.0 nM, DrFe concentrations changed in a much narrower range from 6.8 to 13.3 nM. The annual mean concentrations of DrFe also ranged from 7.1 to 12.6 nM at the 12 sites monitored over the 4 years of the study (2017–2020). Considering the obvious changes in temperature (T), chlorophyll a (Chl a) concentrations (Chl a contents were higher in May, July and September than in March and November), and nutrients over a year in this zone, the consumption of DrFe was expected; the supplement of DrFe observed may have resulted from the transformation of strong organically complexed iron by photoreduction and cell surface reduction. Additionally, a pre-liminary conclusion was drawn based on the theoretical calculation of Fe* that the concentration of DrFe was sufficient to meet the phytoplankton demand.

Fractionation Analysis of Iron in Coastal Rivers to Yantai Sishili Bay with a Bismuth Microrods-Based Electrochemical Sensor - Xueping Hu; Haitao Han; Chenchen Wang; Xingliang Song (Journal of Marine Science and Engineering, 2021)
As an essential metal micronutrient, Fe plays an important role in the marine biogeochemical cycling process, and the bioavailability of Fe has a direct relationship with its fractions in water. The fractionation analysis of iron in main coastal rivers to Yantai Sishili Bay was achieved with an electrochemical sensor based on bismuth microrods (BiMRs). The sensor was characterized by scanning electron microscope and electrochemical methods, and the reliability of the sensor was verified by the determination of the standard samples. Different fractions of iron in coastal river waters, including total iron (TFe), total dissolved iron (TDFe) and particulate iron (PFe), have been determined by combining simple sample pretreatments and cathodic stripping voltammetry with the BiMRs-based sensor. The average concentrations of TFe in Guangdang River, Xin’an River and Yuniao River were 4.02, 3.66 and 4.42 μmol L−1, respectively. The main fractionation of iron in three rivers was PFe, which accounts for 84.46%, 87.56% and 92.34%, respectively. Furthermore, the relationships between iron concentration and tidal action, salinity, dissolved oxygen and other factors were also investigated.

Screening and application of SSR markers related to seed storability traits in maize (Zea mays L.) - Xiaoyang Guo; Xiaohui Sun; Shan Liu; Chengxu Gong; Chenchen Feng; Xiao Han; Tingting Lv; Yu Zhou; Zhenhua Wang; Hong Di (Genetic Resources and Crop Evolution, 2021)

Fracture characterization in oil-based mud boreholes using image logs: example form tight sandstones of Lower Cretaceous Bashijiqike Formation of KS5 well area, Kuqa Depression, Tarim Basin, China - Rui Yuan; Denglin Han; Yangang Tang; Hongxing Wei; Tao Mo; Chenchen Wang (Arabian Journal of Geosciences, 2021)

Species, Spatial-Temporal Distribution, and Contamination Assessment of Trace Metals in Typical Mariculture Area of North China - Dawei Pan; Xiaoyan Ding; Haitao Han; Shenghui Zhang; Chenchen Wang (Frontiers in Marine Science, 2020)

Increasing plant diversity offsets the influence of coarse sand on ecosystem services in microcosms of constructed wetlands - Yuanyuan Du; Bin Luo; Wenjuan Han; Yingyao Duan; Chenchen Yu; Meng Wang; Ying Ge; Jie Chang (Environmental Science and Pollution Research, 2020)

A New Discovery of Ag-Pb-Zn Mineralization via Modern Portable Analytical Technology and Stream Sediment Data Processing Methods in Dajiacuo Area, Western Tibet (China) - Xiaojia Jiang; Xin Chen; Shunbao Gao; Youye Zheng; Huan Ren; Denghui Han; Chenchen Yan; Junsheng Jiang (Journal of Earth Science, 2020)

LncRNA SNHG5 regulates SOX4 expression through competitive binding to miR-489-3p in acute myeloid leukemia - Xiaoyang Ying; Wanggang Zhang; Meiyun Fang; Chenchen Wang; Li Han; Chenmeng Yang (Inflammation Research, 2020)

Stripping Voltammetric Determination of Lead in Coastal Waters With a Functional Micro-Needle Electrode - Haitao Han; Dawei Pan; Ying Li; Jie Wang; Chenchen Wang (Frontiers in Marine Science, 2020)

Anodic stripping voltammetric analysis of different species of copper in seawater using an electrochemical sensor - Xueping Hu; Dawei Pan; Haitao Han; Chenchen Wang (Journal of Oceanography, 2019)

Simultaneous Speciation Analysis of Trace Heavy Metals (Cu, Pb, Cd and Zn) in Seawater from Sishili Bay, North Yellow Sea, China - Haitao Han; Dawei Pan; Shenghui Zhang; Chenchen Wang; Xueping Hu; Yongcong Wang; Fei Pan (Bulletin of Environmental Contamination and Toxicology, 2018)

Vertical profile, contamination assessment of mercury and arsenic in sediment cores from typical intertidal zones of China - Chenchen Wang; Dawei Pan; Haitao Han; Xueping Hu (Environmental Monitoring and Assessment, 2018)

Distribution, sources, and risk assessment of polycyclic aromatic hydrocarbons (PAHs) in surface water in industrial affected areas of the Three Gorges Reservoir, China - Binghui Zheng; Yingqun Ma; Yanwen Qin; Lei Zhang; Yanmin Zhao; Wei Cao; Chenchen Yang; Chaonan Han (Environmental Science and Pollution Research, 2016)

Spatial-temporal variations of phosphorus fractions in surface water and suspended particles in the Daliao River Estuary, Northeast China - Lei Zhang; Yanwen Qin; Chaonan Han; Wei Cao; Yingqun Ma; Yao Shi; Zhichao Liu; Chenchen Yang (Environmental Science and Pollution Research, 2016)